Źródła podziałow we wspolnotach w kontekście społeczno-kulturowym. Czy stosowane nauki społeczne mogą pomoc budować relacje ponad podziałami? = The sources of community divisions in socio-cultural contexts. Can the applied social sciences help build relationships despite the divisions? - Michalski, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article surveys a problem of division in communities examining sources of differences between groups of people and countries in a socio-cultural context. The author describes the impact of culture on the "mind programming" regarding difference, and presents typical categories of cultural aspects like values and practices on various levels of functioning in social realities in terms of thinking and behaviour patterns.
Keywords: podziały; wspólnota; kultura; "zaprogramowanie umysłu"; relacje; wartości; praktyki; divisions; communities; culture; "mind programming"; relationship; values; cultural practices